Analisis Pengendalian Kualitas Untuk Mengurangi Defect Parking Brake dengan Metode FMEA di PT XYZ - Fadhlianty Rachmania Supoyo; Rizki Achmad Darajatun; Wahyudin Wahyudin (Fakultas Teknik, 2023)
PT XYZ is a company operating in the manufacturing industry sector to produce car parking brakes. At this company there are several failures that often occur in the production process, namely bubbles, scratches, bending process failures and press failures. In this study, the aim is to evaluate the failures that occur in the company. The method that will be used in this research is Failure Mode and Effect Analysis (FMEA). FMEA is a method that identifies, analyzes, and prioritizes the failures that occur so that the causes and impacts of each failure will be known. This method produces a Risk Priority Number (RPN) score that starts from the recapitulation results between the severity, occurrence and detection rating values to show the priority level of problems that occur. Based on the RPN calculations carried out in this study, the highest RPN value occurs in the type of bubble defect which is equal to 288. The second rank is the scratch defect type with an RPN score of 180. The third is press failure with an RPN score of 81 and the last is bending failure with a score RPN 40.